Pengaruh Perkembangan Teknologi Informasi dan Teknologi (TIK) terhadap Pengangguran Usia Muda di Indonesia: BPS, Institut Pertanian Bogor - Listari, Silvia Emilia; Pasaribu, Syamsul Hidayat; Novianti, Tanti (Jurnal Ekonomi dan Kebijakan Pembangunan, 2024)
The rapid advancement of information and communication technologies (ICT) is anticipated to effectively solve various economic issues including unemployment in developing countries. However, unemployment in Indonesia has fluctuation and is predominantly affecting the youth population. Additionally, researchers hold different views regarding the impact of ICT development on youth unemployment. Some researchers suggest a positive relationship between ICT and youth unemployment, while others argue that ICT can have detrimental effects on job opportunities and potentially increase youth unemployment. This study aims to describe ICT development and analyze the influence of ICT development on youth unemployment in Indonesia. This research used a dynamic panel methodology and utilizes two indicators of ICT development: mobile phone users and internet users across 33 provinces in Indonesia at 2010-2021. The results of this estimation indicate that mobile phone users and internet users do not significantly impact the youth unemployment model. The variables inflation, foreign and domestic investment and the lagged unemployment have a significant effect on youth enemployment